A conjugate numerical thermal performance analysis of variable spacing battery module with inline arrangement - Afzal, Asif; Agbulut, Umit; Buradi, Abdulrajak; Alwetaishi, Mamdooh; Elumalai, P. V.; Hussain, Fayaz; Kaewthep, Chaloemphol; El-Shafay, A. S.; Bordas, Stephane P. A. (PERGAMON-ELSEVIER SCIENCE LTD, 2026)
The structural arrangement of battery modules is one of the prime factors which helps to select the suitable parameters for thermal management of the battery system. In the present paper four different cases are investigated for a battery module having a variable spacing inline arrangement of 49 battery cells (7 & times; 7). The air inlet velocity of 1 m/s, 2 m/s, 3 m/s, and 4 m/s while battery discharge rate of 1C (5318 W/m3) and 2C (19,452 W/ m3) are selected as prime parameters for study. The computational model used in the present numerical simulation consists of an outer air enclosure and inside this enclosure, a battery module is placed. The finite volume method with second-order upwind scheme is used to solve the equations governing the thermal and fluid flow domain. The pressure-velocity coupling is carried out by SIMPLE algorithm and k-epsilon turbulence model is chosen to capture the air flow through the battery module. The results are plotted for average temperature (Tag), standard deviation in temperature (Tsd), maximum temperature (Tmx), maximum difference in temperature ((Td)mx), and pressure drop (Pdp) between inlet and outlet vents of the enclosure. From the results it is concluded that, for optimal thermal performance of the battery module the structural arrangement of inlet and outlet vent plays a very crucial role. The uniform temperature distribution of battery cells to a greater extent depends on the location of inlet outlet vents as well as on battery discharge rate and inlet velocity. Further it is also observed that the overall operational cost of battery cooling system depends largely on battery module structural arrangement, discharge rate, and flow velocity.
Keywords: Conjugate; Battery module; Inline arrangement; SIMPLE; K -epsilon model; Energy efficiency; ION BATTERY; MANAGEMENT-SYSTEM; MODEL; Thermodynamics; Energy & Fuels; Engineering; Mechanics